Biological carbon pump efficiency in the Humboldt current system off Peru: sediment traps during METEOR cruises M136 and M138 - Anja Engel; Carolina Cisternas-Novoa; Helena Hauss; Rainer Kiko; Frédéric A C Le Moigne (PANGAEA, 2023)
In the ocean, downward flux of particles produced in sunlit surface waters is the major component of the biological carbon pump, which sequesters atmospheric carbon dioxide and fuels deep-sea ecosystems. The efficiency of downward carbon transfer is expected to be particularly high in tropical upwelling systems where hypoxia occurring beneath the productive surface waters is thought to hamper particle consumption. However, observations of both particle feeders and carbon export in low-oxygen waters are scarce. Here, we provide evidence that hypoxia-tolerant zooplankton feed on sinking particles in the extensive Oxygen Minimum Zone off Peru. Using several arrays of drifting sediment traps and in situ imaging, we show geochemical and morphological transformations of sinking particles and substantial control of carbon export by zooplankton. Our findings challenge the assumption of a consistently efficient biological carbon pump in OMZs and further demonstrate the need to consider mesopelagic organisms extquotesingle adaptations when studying oceanic carbon sequestration.